Sex, Gender, Genetics, and Health - Short, Susan E. (American Public Health Association, 2013)
This article addresses 2 questions. First, to what extent are sex and gender incorporated into research on genetics and health? Second, how might social science understandings of sex and gender, and gender differences in health, become more integrated into scholarship in this area? We review articles on genetics and health published in selected peer-reviewed journals. Although sex is included frequently as a control or stratifying variable, few articles articulate a conceptual frame or methodological justification for conducting research in this way, and most are not motivated by sex or gender differences in health. Gender differences in health are persistent, unexplained, and shaped by multilevel social factors. Future scholarship on genetics and health needs to incorporate more systematic attention to sex and gender, gender as an environment, and the intertwining of social and biological variation over the life course. Such integration will advance understandings of gender differences in health, and may yield insight regarding the processes and circumstances that make genomic variation relevant for health and well-being.